MAPPING OF TUBERCULOSIS DISEASE WITH GEOGRAPHIC INFORMATION SYSTEM IN KAPANEWON BANGUNTAPAN, SEWON, AND KASIHAN AREAS - Sari, Ana Dewi Lukita; Arifin, Zainal; Rahmatullah, Widia; Handayani, Reska (Jurnal Kesehatan Saintika Meditory, 2025)
Banguntapan, Kasihan and Sewon Sub-districts have experienced an increase or high cases of tuberculosis in the last 3 years because one of the factors is population density, because the 3 sub-districts are urban areas or directly border the city. The Health Office also has a program to reduce the transmission of tuberculosis in Bantul Regency, by providing assistance, socialization and tracking related to tuberculosis together with the local health center. The purpose of this study was to find out information about the process of collecting health data on tuberculosis cases, making graphs of tuberculosis cases based on gender and age, analyzing supporting factors for tuberculosis based on environmental factors (rainfall). This type of research is qualitative descriptive research with a case study research design. The subjects of this study were officers of the Prevention and Control of Infectious Diseases (P2PM) or those responsible for tuberculosis disease at the Bantul Regency Health Office and programmers holding tuberculosis disease reporting at the Banguntapan, Kasihan and Sewon Health Centers. The object of this study was data on the 3 largest tuberculosis cases in Bantul Regency. The data collection techniques used were interviews, observations and documentation studies. The process of collecting health data on tuberculosis cases at the Bantul District Health Office and Community Health Centers in each sub-district has been carried out computerized and online using the SITB application. The distribution of tuberculosis cases based on sub-district areas is high in the Banguntapan Sub-district area, there are 60 cases with the highest cases in Banguntapan Village as many as 20 cases (33.3%), in the Sewon Sub-district area there are 45 cases with the highest cases in Panggungharjo Village as many as 17 cases (37.7%), in the Kasihan Sub-district area there are 36 cases with the highest cases in Ngestiharjo Village as many as 12 cases (36.1%). Environmental factors that influence the spread of tuberculosis in Bantul Regency areas, especially in Banguntapan, Sewon, and Kasihan Sub-districts, are rainfall.